Spell corrector for Bangla language using Norvig’s algorithm and Jaro-Winkler distance - Istiak Ahamed; Maliha Jahan; Zarin Tasnim; Tajbia Karim; S. M. Salim Reza; Dilshad Ara Hossain (Institute of Advanced Engineering and Science, 2021)
In the online world, especially in the social media platform most of us write without much regard to correct spelling and grammar. The spelling mistakes are much larger in proportion when it comes to Bangla language. In our paper, we presented a method for error detection and correction in Bangla words' spellings. Our system could detect a misspelled Bangla word and provide two following services-suggesting correct spellings for the word and correcting the word. We had used Norvig's algorithm for the purpose but instead of using probabilities of the words to prepare the suggestions and corrections, we had used Jaro-Winkler distance. The previous works done in this field for Bangla language are either very slow or offers less accuracy. Our system successfully achieved a 97% accuracy when evaluated with 1000 Bangla words.